Exosome-Mediated eCIRP Release From Macrophages to Induce Inflammation in Sepsis - Murao, Atsushi; Tan, Chuyi; Jha, Alok; Wang, Ping; Aziz, Monowar (Frontiers in Pharmacology, 2021)
Extracellular cold-inducible RNA-binding protein (eCIRP) is an important damage-associated molecular pattern (DAMP). Despite our understanding of the potentially harmful effects of eCIRP in sepsis, how eCIRP is released from cells remains elusive. Exosomes are endosome-derived extracellular vesicles, which carry proteins, lipids, and nucleic acids to facilitate intercellular communication and several extracellular functions. We hypothesized that eCIRP is released via exosomes to induce inflammation in sepsis. Exosomes isolated from the supernatants of LPS-treated macrophage culture and serum of endotoxemia and polymicrobial sepsis mice showed high purity, as revealed by their unique median sizes ranging between 70-126 nm in diameter. eCIRP levels of the exosomes were significantly increased after LPS treatment in the supernatants of macrophage culture, mouse serum, and cecal ligation and puncture (CLP)-induced sepsis mouse serum. Protease protection assay demonstrated the majority of eCIRP was present on the surface of exosomes. Treatment of WT macrophages and mice with exosomes isolated from LPS-treated WT mice serum increased TNFα and IL-6 production. However, treatment with CIRP-/- mice serum exosomes significantly decreased these levels compared with WT exosome-treated conditions. CIRP-/- mice serum exosomes significantly decreased neutrophil migration in vitro compared with WT exosomes. Treatment of mice with serum exosomes isolated from CIRP-/- mice significantly reduced neutrophil infiltration into the peritoneal cavity. Our data suggest that eCIRP can be released via exosomes to induce cytokine production and neutrophil migration. Thus, exosomal eCIRP could be a potential target to inhibit inflammation.